1997
DOI: 10.1128/mcb.17.8.4346
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Atypical Protein Kinase C Isoforms in the UV-Induced Apoptotic Signaling Cascade

Abstract: Recent studies have documented the involvement of the atypical protein kinase C (aPKC) isoforms in important cellular functions such as cell proliferation and survival. Exposure of cells to a genotoxic stimulus that induces apoptosis, such as UV irradiation, leads to a profound inhibition of the atypical PKC activity in vivo. In this study, we addressed the relationship between this phenomenon and different proteins involved in the apoptotic response. We show that (i) the inhibition of the aPKC activity preced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
132
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(142 citation statements)
references
References 58 publications
9
132
1
Order By: Relevance
“…Deprivation of neurotrophic factors or UV irradiation not only activates stress kinase cascades but also leads to dramatic inhibition of the ERK pathway (13). Furthermore, ERK expression in NIH 3T3 cells impairs the majority of the UV-induced apoptotic response (14). The prosurvival function of ERK was confirmed in a recent report showing that inhibition of ERK signaling leads to increased sensitivity to cisplatin (cis-diammine-dichloroplatinum) in ovarian cancer cells (31).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Deprivation of neurotrophic factors or UV irradiation not only activates stress kinase cascades but also leads to dramatic inhibition of the ERK pathway (13). Furthermore, ERK expression in NIH 3T3 cells impairs the majority of the UV-induced apoptotic response (14). The prosurvival function of ERK was confirmed in a recent report showing that inhibition of ERK signaling leads to increased sensitivity to cisplatin (cis-diammine-dichloroplatinum) in ovarian cancer cells (31).…”
Section: Discussionmentioning
confidence: 50%
“…In addition, ERK is required for survival signaling in response to cellular growth factors (13). Furthermore, overexpression of ERK in NIH 3T3 cells largely impairs the UV-induced apoptotic response (14). Thus, it seems that the cell fate (i.e., death or survival) is decided by a critical balance between the ERK pathway and the JNK or p38 MAPK pathway.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that Par-4 speci®cally inhibits PKC isoforms x and l/i but not others, thereby interrupting signaling to AP1 and inducing apoptosis (Berra et al, 1997). It is conceivable that Par-4 interconnects di erent signaling pathways.…”
Section: The Leucine Zipper As Interaction Domain In Transcription Famentioning
confidence: 71%
“…[15][16][17][18][19] The chondrocyte pro-and antiapoptotic functions of p38 kinase and PKCz, respectively, are also observed in other cell types. [21][22][23][24] Evidence that PKCz provides survival signals in chondrocytes is supported by the observations that ectopic expression of wild-type or constitutively active PKCz inhibited NO-induced apoptosis of articular chondrocytes, whereas inhibition of PKCz activity by PS-PKCz potentiated NO-induced apoptosis. 15 Currently, underlying molecular mechanism leading to the inhibition of p38 kinase-induced apoptosis of chondrocyte by PKCz is not known.…”
Section: Discussionmentioning
confidence: 97%